Insectos agalladores asociados al dosel en hábitats xéricos y mésicos de bosques sobre arena blanca, Reserva Nacional Allpahuayo-Mishana, Perú - Panduro Bardales, Áaron Hafid Jesús (2024)
The present work carried out in the Allpahuayo-Mishana National Reserve, between the months of January to December 2022. The general objective was evaluate the diversity of gill-insects associated to the canopy of xeric and mesic habitats of forests on white sand, testing whether the Diversity of these insects is higher in xeric than in mesic habitats, as predicted by the higrotermal stress hypothesis. All plant individuals with a DAP ≥10 cm (diameter at breast height) belonging to 16 plots of 5x20 m; 98 morphotypes of insect galls were recorded, with 53 (54.1%) morphotypes for the mesic habitat, and 44 (44.9%) morphotypes for the xeric habitat. It also observed 01 morphotype in both habitats. Cecidomyiidae (Diptera) was the only inducer family identified and Fabaceae had the highest richness (25) of gall morphotypes. According to the data obtained, it concluded that there was no statistically significant difference in gall insects between the types of habitats.